Citrulline as a biomarker of bacteraemia during induction treatment for childhood acute lymphoblastic leukaemia. Issue 1 (5th November 2020) - De Pietri, Silvia; Frandsen, Thomas Leth; Christensen, Mette; Grell, Kathrine; Rathe, Mathias; Müller, Klaus
Abstract: Background: Systemic infections are a major cause of morbidity in children with acute lymphoblastic leukaemia (ALL). However, identification of patients at increased risk is still a challenge. Knowing that both neutropaenia and gastrointestinal toxicity are risk factors for bacteraemia, we aimed at comparing absolute neutrophil counts (ANC) and plasma citrulline levels (indicating enterocyte loss) in children with ALL with and without bacteraemia during induction treatment. Procedure: We prospectively included 61 children with ALL treated according to the Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL‐2008 protocol. ANC and plasma C‐reactive protein (CRP) were measured on treatment days 1, 8, 15, 22 and 29. Plasma citrulline was measured on days 1, 8, 15 and 29. Bacteraemia episodes during induction treatment were recorded retrospectively. Results: Nineteen of sixty‐one (31%) patients experienced bacteraemia occurring on median day 13 (range 5‐20). Patients with bacteraemia during induction treatment had lower citrulline level on day 15 ( P < .01) compared to patients without bacteraemia, indicating more severe enterocyte loss. Nevertheless, ANC was similar in the two patient groups on days 8 and 15. CRP was negatively correlated with same‐day citrulline ( P < .03 for all) and ANC ( P < .04 for all). Conclusions: During chemotherapy‐induced neutropaenia, plasma citrulline may help identify patients at increased risk of bacteraemia.